A novel prognostic index of hepatocellular carcinoma based on immunogenomic landscape analysis. Issue 4 (27th August 2020) - Xiao, Han; Wang, Ben; Xiong, Hai‐Xia; Guan, Jia‐Fu; Wang, Jian; Tan, Tao; Lin, Kang; Zou, Shu‐Bing; Hu, Zhi‐Gang; Wang, Kai
Abstract: Changes in immune responses to hepatocellular carcinoma (HCC) are closely related to the occurrence, development, and prognosis of this disease. Exploring the role of immune‐related genes (IRGs) in HCC would provide insights into the mechanisms regulating this disease. The Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) provide a platform for such research, owing to a large number of HCC samples available for comprehensive and systematic immunogenomics analyses. We analyzed the IRGs expression profile and clinical information of patients with HCC based on the TCGA and ICGC database. Potential molecular mechanisms and properties of the screened IRGs were analyzed across multiple databases. And we analyzed the correlation between IRGs, single‐nucleotide polymorphisms, and copy number variation. A novel prognostic index, based on IRGs, was developed using the LASSO Cox regression algorithm, followed by univariate and multivariate Cox regression analyses to analyze the prognostic index. Information in the ICGC database was used to verify the reliability of the prognostic index. A total of 54 differentially expressed IRGs were found to be significantly associated with HCC prognosis, and there is a significant correlation between their expression level and copy number variation. Functional enrichment analyses indicated that the genes play active roles in tumor and immune‐related signaling pathways. In addition, five potential biomarkers namely IRG, MAPK3, HSP90AA1, HSP90AB1, HSPA4, and CDK4, were identified. Finally, a novel prognostic index, based on IRGs (PSMD14, FABP6, ISG20L2, HGF, BIRC5, IL17D, and STC2), was found useful as an independent prognostic factor, not only for prognosis but also to reflect levels of infiltration in a variety of immune cells. Our team conducted a genomics study of IRGs in HCC and screened several clinically significant IRGs, and our model provides an effective approach for stratification and characterization of patients using IRG‐based immunolabeling tools to monitor the prognosis of HCC. Abstract : Our team conducted a genomics study of immune‐related genes (IRGs) in hepatocellular carcinoma (HCC) and screened several clinically significant IRGs, and our model provides an effective approach for stratification and characterization of patients using IRG‐based immunolabeling tools to monitor the prognosis of HCC.